2017
DOI: 10.3390/pharmacy5020016
|View full text |Cite
|
Sign up to set email alerts
|

Developing Professional Identity in Undergraduate Pharmacy Students: A Role for Self-Determination Theory

Abstract: Professional identity development, seen as essential in the transition from student to professional, needs to be owned by the universities in order to ensure a workforce appropriately prepared to provide global health care in the future. The development of professional identity involves a focus on who the student is becoming, as well as what they know or can do, and requires authentic learning experiences such as practice exposure and interaction with pharmacist role models. This article examines conceptual fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 49 publications
2
57
0
Order By: Relevance
“…16 Research with a focus on pedagogies, which support the individual (psychological) level is lacking, therefore a framework that is informed by an understanding of the mechanism behind individual identity development is needed. 16 To address this issue, Mylrea and colleagues 17 have proposed Deci and Ryan's 18,19 self-determination theory (SDT) as a relevant framework upon which to base pedagogical approaches to PIF.…”
Section: -13mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Research with a focus on pedagogies, which support the individual (psychological) level is lacking, therefore a framework that is informed by an understanding of the mechanism behind individual identity development is needed. 16 To address this issue, Mylrea and colleagues 17 have proposed Deci and Ryan's 18,19 self-determination theory (SDT) as a relevant framework upon which to base pedagogical approaches to PIF.…”
Section: -13mentioning
confidence: 99%
“…17 The program employed autonomy-supportive teaching 22 techniques and was designed to provide students in their first year of study with the opportunity to begin to think, act and feel like a pharmacist. This study also evaluated the PIP and tested the hypothesis that the introduction of the PIP across the first two years of a pharmacy program would increase student professional identity and autonomy.…”
Section: -13mentioning
confidence: 99%
“…The educational environment has been reported to enhance SD motivation in health professional education [ 9 , 18 ]. A learning environment focusing on patient-centered education seems to improve both deep and active learning as well as IM [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, learning motivation is an important factor for continued professional learning in the future [ 6 ]. Some reports on the learning process and learning motivation profiles of medical and nursing students have been published [ 7 , 8 ] and a few studies have also reported on pharmacy students [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Professional identity formation, which is the development of professional values, actions, and aspirations, is gaining momentum as a movement for health professions educational reform. [1][2][3][4][5] Nowhere is this movement stronger than in medical education. [1][2][3] In 2010, the Carnegie Foundation brought the issue to the forefront, stating: "professional identity formation should be the backbone of medical education."…”
Section: Introductionmentioning
confidence: 99%